Process Models and Distribution of Work in Offshoring Application Software Development - Karl Kurbel (European University Viadrina, Department of Business Administration and Economics, 2007)
Common process models for the development of application software (AS) are examined as to how well they are suited for offshoring projects. The need for communication and interaction among onsite and offshore project stakeholders is identified as a critical success factor. Process models used by organizations providing offshoring services are discussed, and a generalized offshoring life cycle model is developed. A specific focus is set on the distribution of work between the organization that outsources AS development and the offshore organization that carries out the major share of the development work. Problems and challenges that have to be faced, making offshoring a difficult task, are discussed.
Keywords: 330; Programmierung; Geschäftsprozess; Offshoring; Projektmanagement; Arbeitsteilung; Theorie